The Chinese Ultimatum - McGhee, Edward and Moore, Robin (London Sphere Bookd Ltd., 1978)
The Russians and the Chinese clash in a "limited" war. Germany and Japan join the battle. Nuclear weapons are threatened...and U.S. leaders must decide between helping the Russians or the Chinese.
Keywords: English Fiction